Participants’ experiences and impressions of a group-based positive psychology intervention programme for rural adults in Ghana - Appiah, R.; Fadiji, A.W.; Wissing, M.P.; Schutte, L. (Taylor & Francis Group, 2021)
Introduction: There is growing evidence that group-based mental health intervention programmes can encourage the development of peer support, psychosocial skills, and collaborative therapeutic relationships with longer lasting effects. This study explored participants’ experiences of, perceived benefits of, and recommendations to improve a 10-session group based multicomponent positive psychology intervention (mPPI)—the Inspired Life Programme (ILP)—designed to promote positive mental health and reduce symptoms of depression and negative affect in a sample of rural Ghanaian adults. Method: Face-to-face semi-structured individual interviews were conducted with 18 randomly selected programme participants three months after their participation in the ILP. Data were analysed thematically with an inductive approach. Results: Participants described their experience of the ILP as a forum for growth that granted them the opportunity to introspect, practicalise and situate everyday life challenges, connect with others, and to develop a sense of mutual accountability. Results indicate that the ILP led participants to develop a stronger sense of positivity and well-being, fructify their ideas, and to cultivate stronger social networks and relationships that led to increased vocational productiveness. Participants recommended that researchers include facets of physical health promotion in the programme and invite close relations of participants to participate in the programme. Conclusion: This study provides the first insight into participants’ experiences of a group based mPPI in Ghana. These findings may provide useful information to inform the design of context-appropriate community-based mental health interventions to fit participants’ specific needs, capacities, and circumstances.
Research Article
Keywords: Positive psychology; intervention; participants’ experiences; mental health; rural poor adults; qualitative study; inspired life programme; Ghana